Modified Orthogonal Space-Time Block Codes for Time-Selective Fading Channels - Villardi, Gabriel Porto; De Abreu, Giuseppe T. F.; Kohno, Ryuji (IEEE transactions on vehicular technology, 2008)
We consider orthogonal space-time block codes (O-STBCs) in time-selective fading channels and propose a modified O-STBC (MO-STBC), which is less subject to the performance degradation caused by symbol-by-symbol channel variation. It is shown both analytically and through computer simulations that MO-STBCs effectively reduce the loss of orthogonality affecting O-STBCs in the symbol-by-symbol time-selective channel. MO-STBCs are systematically constructible for any number of antennas and have the same decoding complexity of conventional O-STBCs. The bit-error-rate (BER) performance of MO-STBCs over time-selective fading channels of generalized statistics, with Gray-code-mapped M-ary phase-shift-keying (PSK) modulation and quadratic-amplitude modulation (QAM), is analytically derived. Moreover, MO-STBCs can also easily be combined with existing linear O-STBC decoders specifically designed for the time-selective channel, yielding significant performance improvement over conventionally constructed and decoded O-STBCs.